Teacher Strategies for Overcoming Students' Learning Difficulties in Islamic Religious Learning in Junior High Schools - Suriati, Suriati; Kardi, Juliwis; Rahman, Taufik (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2024)
Difficulties faced by students in Islamic religious education subjects. In terms of process, it is difficult to understand the material, students have difficulty with material related to Al-Qur'an verses or reading and writing, the Al-Qur'an, especially the ability to memorize it. This research aims to describe the strategies of Islamic Religious Education teachers in overcoming students' learning difficulties, namely taking a direct approach with students, providing understanding and guidance about religious knowledge through various methods, providing guidance through the tahfiz program once a week, and then carrying out evaluations. This research uses descriptive qualitative methods of data collection in the form of interviews, documentation, and observation. The analytical techniques used are data collection, data reduction, data presentation, and conclusion. To ensure the validity of the research data, source triangulation was used. The results of the analysis show that the types of learning difficulties faced by students in Islamic Religious Education subjects at Madrasah Tsanawiyah Negeri Padang Panjang are difficulties in understanding the material, difficulties in memorizing verses and hadiths and their meanings, methods used by teachers in overcoming students' learning difficulties in Education subjects The Islamic religion at Madrasah Tsanawiyah Negeri Padang Panjang is through tutoring outside of learning hours, creating a pleasant class atmosphere, and always motivating students. The results of this research can be used as initial data for subsequent researchers in studying problems in different contexts and issues.